The prognostic ability of the STarT Back Tool was affected by episode duration - Morso, L.; Kongsted, A.; Hestbaek, L.; Kent, Peter (Springer, 2016)
Purpose: The prognostic ability of the STarT Back Tool (SBT) reportedly varies, but the factors affecting this are unclear. This study investigated the influences of care setting (chiropractic, GP, physiotherapy, spine centre), episode duration (0–2, 3–4, 4–12, > 12 weeks), and outcome time period (3, 6, 12 months) on SBT prognostic ability. Methods: This was a secondary analysis of data from three primary care cohorts [chiropractic (n = 416), GP (n = 265), and physiotherapy (n = 200) practices] and one cohort from a secondary care outpatient spine centre (n = 974) in Denmark. Care pathways were not systematically affected by SBT risk subgroup (non-stratified care). Using generalised estimating equations, we investigated statistical interactions between SBT risk subgroups and potentially influential factors on the prognostic ability of the SBT subgroups, when Roland Morris Disability Questionnaire scores were the outcome. Results: SBT risk subgroup, age, care setting, and episode duration were all independent prognostic factors. The only investigated factor that modified the prognostic ability of the SBT subgroups was episode duration. Conclusions: These results indicate that the prognostic ability of the SBT in these non-stratified care settings was unaffected by care setting on its own. However, the prognosis of patients is affected by diverse clinical characteristics that differ between patient populations, many of which are not assessed by the SBT. When controlling for some of those factors and testing potential interactions, the results showed that only episode duration affected the SBT prognostic ability and, specifically, that the SBT was less predictive in very acute patients ( < 2 weeks duration).